KEHARUSAN IKRAR TALAK DI DEPAN MAJELIS HAKIM PENGADILAN AGAMA: Perspektif Maqashid Syari'ah Ibnu Asyur - Ludfi, ludfi (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2023)
This study aims to elaborate on the provisions of divorce in classical fiqh, which are considered valid upon the husband's pronouncement alone, in contrast to positive law, where divorce is only considered valid if declared before a court. This discrepancy creates a legal dilemma among Indonesian Muslims, prompting the application of maqāṣid syarī‘ah as a reconciliatory framework through the perspective of Ibn ‘Āshūr. The research employs a library-based method using content analysis, philosophical-hermeneutic, and maqāṣid syarī‘ah approaches. Data were collected through documentation involving inventory, classification, and evaluation of relevant sources. The findings indicate that requiring divorce to be pronounced before the Panel of Judges of the Religious Courts aligns with the principle of maṣlaḥaḥ, supporting legal equality and certainty—particularly regarding marital status, spousal maintenance, joint assets, ḥaḍānah rights, and child support. Ibn ‘Āshūr’s framework, built upon the four pillars of al-Fiṭrah, as-Samāḥah, al-Musāwah, and al-Ḥurriyyah, emphasizes the importance of witnesses in interpreting QS. aṭ-Ṭalāq (65):2 through ẓāhir al-naṣṣ. Although he does not explicitly require divorce to be declared before a court, this interpretation supports the relevance of court-based divorce procedures in Indonesia as a means to preserve the objectives of Islamic law (maqāṣid syarī‘ah) by discouraging arbitrary divorce.